Perception and effects of traffic noise in Miraflores District, Perú - Saavedra Ramírez, Letis (2022)
The purpose of this research was to evaluate the perception and effects of noise in a specific community, for which we used structured noise surveys and measurements of sound pressure levels. Road traffic was the main source of noise and annoyance, followed by building activities. Sleep disturbance was the most negative effect caused by noise. Through the Traffic Noise Index, it was determined that 100% of the evaluated area is above the prohibitive noise limits.